THE INFLUENCE OF AUDIT COMPETENCY AND WORK EXPERIENCE ON COMPUTER-ASSISTED AUDIT TECHNIQUES AND THEIR IMPACT ON AUDIT QUALITY AT THE BPK REPRESENTATIVE OFFICE OF NORTH SUMATRA PROVINCE - Rizqi Anggraini; Eka Nurmala Sari; Irfan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine, analyze and test the effect of auditor competence and work experience on computer-assisted audit techniques and their impact on audit quality. This type of research is quantitative. This research was conducted using a survey method by distributing questionnaires to auditors working at BPK representative office in North Sumatra Province. Sampling using saturated sampling with a total of 95 respondents. Data analysis was performed using path analysis techniques by using the SPSS program. The results of this research to show that work experience affects computer-assisted audit techniques, computer-assisted audit techniques affect audit quality, auditor competence affects audit quality, work experience affects audit quality. However, the auditor competence has no effect on computer-assisted audit techniques. The results of the Sobel test also prove that work experience affects audit quality through computer-assisted audit techniques but the auditor competence does not affect audit quality through computer-assisted audit techniques. These results conclude that computer-assisted audit techniques can mediate (intervening) work experience on audit quality.